Evolution from discrete mononuclear complexes to trinuclear linear cluster and 2D coordination polymers of Mn(II) with dihydrazone Schiff bases: Preparation, structure and thermal behavior. (15th September 2021) - Croitor, Lilia; Cocu, Maria; Bulhac, Ion; Bourosh, Paulina N.; Ch. Kravtsov, Victor; Petuhov, Oleg; Danilescu, Olga
Graphical abstract: The preparation, structural diversity and thermal behavior of two discrete compounds and two coordination polymers with hydrazone Schiff bases derived from 2, 6-diacetylpyridine and isonicotinic/nicotinic hydrazides are reported and discussed. Abstract: Four Mn(II) coordination compounds based on the 2, 6-diacetylpyridine bis(isonicotinoylhydrazone) (H2 L 1 ) and 2, 6-diacetylpyridine bis(nicotinoylhydrazone) (H2 L 2 ), were prepared using different synthetic conditions and starting manganese salts: discrete mononuclear [Mn(H2 L 1 )2 (H2 O)2 ](NO3 )2 (1 ) and trinuclear [Mn3 (H2 L 1 )2 (NCS)2 Cl4 (H2 O)2 ] (2 ) complexes and two 2D coordination polymers {[Mn3 (L 1 )3 (H2 O)2 ]·1.5C2 H5 OH}n (3 ) and {[MnL 2 ]·dmf}n (4 ), where dmf = N, N-dimethylformamide. Single-crystal X-ray diffraction study shows that H2 L 1 and H2 L 2, which differ only by para- or meta- position of radicals with respect to the nitrogen atoms in the terminal pyridyl fragments, demonstrate chelate or chelate-bridging coordination mode with N3 O2, or N4 O2 and N5 O2 donor atoms, respectively. The planar-chelate coordination of these ligands provides the pentagonal-bipyramidal surrounding of Mn(II) and the terminal pyridyl moieties promote bridging function and structure expansion in 2 –4 as well as octahedral Cl2 N4 coordination geometry for one of Mn(II) atoms in the trinuclear complex 2 . All compounds have been investigated in the solid state by IR spectroscopy and thermal analysis in order to understand the influence of the inorganic anion presence/absence on the stability of synthesized compounds.